The impact of interventions for youth experiencing homelessness on housing, mental health, substance use, and family cohesion: a systematic review - Jean Zhuo Wang; Sebastian Mott; Olivia Magwood; Christine Mathew; Andrew Mclellan; Victoire Kpade; Priya Gaba; Nicole Kozloff; Kevin Pottie; Anne Andermann (BMC, 2019)
Abstract Background Youth often experience unique pathways into homelessness, such as family conflict, child abuse and neglect. Most research has focused on adult homeless populations, yet youth have specific needs that require adapted interventions. This review aims to synthesize evidence on interventions for youth and assess their impacts on health, social, and equity outcomes. Methods We systematically searched Medline, Embase, PsycINFO, and other databases from inception until February 9, 2018 for systematic reviews and randomized controlled trials on youth interventions conducted in high income countries. We screened title and abstract and full text for inclusion, and data extraction were completed in duplicate, following the PRISMA-E (equity) review approach. Results Our search identified 11,936 records. Four systematic reviews and 18 articles on randomized controlled trials met the inclusion criteria. Many studies reported on interventions including individual and family therapies, skill-building, case management, and structural interventions. Cognitive behavioural therapy led to improvements in depression and substance use, and studies of three family-based therapies reported decreases in substance use. Housing first, a structural intervention, led to improvements in housing stability. Many interventions showed inconsistent results compared to services as usual or other interventions, but often led to improvements over time in both the intervention and comparison group. The equity analysis showed that equity variables were inconsistently measured, but there was data to suggest differential outcomes based upon gender and ethnicity. Conclusions This review identified a variety of interventions for youth experiencing homelessness. Promising interventions include cognitive behavioural therapy for addressing depression, family-based therapy for substance use outcomes, and housing programs for housing stability. Youth pathways are often unique and thus prevention and treatment may benefit from a tailored and flexible approach.